Penegakan Hukum Kasus Lowongan Kerja Fiktif Berdasarkan Undang-Undang Nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang - Dewi, Wulan Kusuma; Airlangga, Rendy (Universitas Batanghari Jambi, 2026)
This study examines the increasing cases of human trafficking carried out through the modus of fake job vacancies in Indonesia. The purpose of this research is to assess the implementation of law enforcement in handling such cases and to evaluate the effectiveness of both preventive and repressive measures taken by the relevant authorities. The study employs a normative juridical method with a statutory and case approach, complemented by interviews with prosecutors to obtain practical insights into enforcement mechanisms. The findings indicate that preventive efforts include public awareness campaigns, the enhancement of digital literacy, and stricter supervision of online job advertisements. Meanwhile, repressive measures are implemented by prosecuting perpetrators under Law Number 21 of 2007 on the Eradication of the Crime of Human Trafficking. However, obstacles remain, particularly in the form of suboptimal interagency coordination and insufficient victim protection. This research concludes that effective law enforcement requires integrated cooperation between the government and society to ensure legal certainty and the fulfillment of victims’ rights.